Developing and Assessing a Sustainable Strategy for Yasuj City: Integrating SWOT, Strategic Position and Action Evaluation Matrix, and Scenario Planning - Salamatnia, Arezoo; Balist, Jahanbakhsh; Nahavandchi, Mehrdad (Urban Planning and Construction, 2025)
The cultural and natural features of Yasuj, as well as its young and educated population, make the city a promising example of sustainable urban growth in Iran. However, limitations such as poor urban management, inadequate infrastructure, and slow economic growth limit its potential. This study aims to assess the urban management of Yasuj and to develop a sustainable development strategy using SWOT (Strengths, Weaknesses, Opportunities, and Threats) and SPACE (Strategic Position and Action Evaluation) analysis. The research uses a descriptive-analytical approach and focuses on applied development. Data was collected from 40 urban planning professionals through on-site observations, document review, and questionnaires. The internal (Internal Factor Evaluation [IFE] = 2.10) and external (External Factor Evaluation [EFE] = 2.37) elements of Yasuj are below average, indicating a defensive strategic position that requires a review of policy and institutional structures. The report identifies potential in tourism, agriculture, and science and proposes solutions such as improving inter-agency cooperation, increasing public engagement, and investing in eco- and agro-tourism. Scenario planning using SWOT, SPACE, and AHP (Analytic Hierarchy Process) has helped to develop adaptive strategies for optimistic, moderate, and pessimistic futures. Realizing the vision of sustainable development of Yasuj requires collective efforts, continuous collaboration and strategic coordination among all local stakeholders, enhancing expertise and research capacity within academic institutions, and fostering effective and genuine partnerships among government, private and civil society sectors to ensure the continuous improvement of the quality of life of residents while preserving the identity, culture and ecosystem of the region.